2018
DOI: 10.7150/thno.28029
|View full text |Cite
|
Sign up to set email alerts
|

Targeted homing of CCR2-overexpressing mesenchymal stromal cells to ischemic brain enhances post-stroke recovery partially through PRDX4-mediated blood-brain barrier preservation

Abstract: Rationale: Mesenchymal stromal cells (MSCs) are emerging as a novel therapeutic strategy for the acute ischemic stroke (AIS). However, the poor targeted migration and low engraftment in ischemic lesions restrict their treatment efficacy. The ischemic brain lesions express a specific chemokine profile, while cultured MSCs lack the set of corresponding receptors. Thus, we hypothesize that overexpression of certain chemokine receptor might help in MSCs homing and improve therapeutic efficacy. Methods: Using the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
57
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(62 citation statements)
references
References 83 publications
(94 reference statements)
4
57
0
Order By: Relevance
“…6a). Functional recovery was first assessed by the Menzies score as previously described 32,33 , and greater improvement of the neurological deficits was detected in the hPSC-CNC PC and HBVP groups than in the human dermal fibroblast (HDF) and phosphate-buffered saline (PBS) groups at day 3 post stroke, and no significant difference was found between hPSC-CNC PC group and HBVP group (Fig. 6b).…”
Section: Pax3 Sox10mentioning
confidence: 93%
“…6a). Functional recovery was first assessed by the Menzies score as previously described 32,33 , and greater improvement of the neurological deficits was detected in the hPSC-CNC PC and HBVP groups than in the human dermal fibroblast (HDF) and phosphate-buffered saline (PBS) groups at day 3 post stroke, and no significant difference was found between hPSC-CNC PC group and HBVP group (Fig. 6b).…”
Section: Pax3 Sox10mentioning
confidence: 93%
“…The pMCAO-miR-182 KD group had significantly attenuated the extravasation of Evans blue compared with the pMCAO-WT group ( Figure 2B). Because astrocyte end-feet and endothelial cells TJ proteins are essential for the maintenance of BBB homeostasis, 35,36 we examined the structural integrity of the BBB through double-staining of endothelial cells and astrocytes. The results showed that the BBB structure was relatively complete in the sham group, while the pMCAO-miR-182 KD group had more BBB structures in the infarction area compared with the pMCAO-WT group ( Figure 2C).…”
Section: Mir-182 Knockdown In Mice Reduced Infarct Volume and Presementioning
confidence: 99%
“…CCL2 is constitutively present in the normal brain and within neurons, astrocytes, and endothelial cells; however, it is upregulated during a stroke [ 17 , 18 , 19 ]. Increases in CCL2 level induce the recruitment of various inflammatory cells to the brain and disruption of the BBB after stroke [ 10 , 20 ]. This migration of inflammatory cells is promoted by CCL2/CCR2 interactions, which induces translocation of CCR2-expressing inflammatory cells into infarct areas already experiencing increased CCL2 expression following a stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Previously studies suggest that increased CCL2 levels in stroke exacerbate neuro-inflammation and subsequent brain injury, thereby increasing stroke volume and resulting in poor prognosis [ 21 , 22 ]. However, recent studies show that CCL2/CCR2 interaction positively affects functional recovery from stroke [ 23 , 24 ], and other studies confirm that CCL2 promotes the homing of CCR2-expressing stem cells from the bone marrow to the damaged brain, which contributes to brain repair following stroke [ 20 , 25 , 26 ]. Additionally, this interaction promotes intravascular migration of stem cells into the injury sites and is essential for the therapeutic homing of CCR2-expressing stem cells [ 6 , 7 , 11 , 27 , 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation